Potential risks arising from prolonged use of over-the-counter medications (MIPS) for pain relief: A surprising analysis through literature review (Research, Society and Development, 2023)
The use of medication is a resource widely used by society to combat a series of health problems, ranging from self-limited problems to minor disorders. Minor disorders are self-limited problems, which are acute in nature, low in severity and tend to resolve themselves without causing much harm to the patient. The treatment of minor disorders may involve non-pharmacological and pharmacological measures and, in the latter case, it is common for patients to resort to Over-the-Counter Medications (MIPs). This project's main objective is to propose a comprehensive analysis of the existing scientific literature, aiming to identify and consolidate data that substantiate the significant health risks associated with the continuous use of MIP aimed at treating pain. To this end, we carried out an extensive literature review in the electronic databases SciELO, LILACS and BVS, explored in search of studies that specifically addressed the risks associated with the prolonged use of MIPs for the treatment of pain. The main medications used are acetylsalicylic acid, dipyrone, ibuprofen, naproxen and paracetamol. Among the risks associated with the misuse of these medications are delays in the diagnosis of serious illnesses, increased risk of chemical dependency and tolerance to the medication; drug poisoning; and allergic reactions, problems such as bleeding, liver damage, spinal cord aplasia and hemolytic anemia. Therefore, the pharmaceutical professional emerges as a central figure in mitigating the problems associated with self-medication with MIPs, so that their actions play a vital role in preventing complications arising from the inappropriate use of these medications.